Lifestyle Behaviours, Self-Esteem and Academic Performance in Primary Education Students-A Structural Equation Model According to Sex and School Type - Gracia Cristina Villodres; Federico Salvador-Pérez; Ramón Chacón-Cuberos; José Joaquín Muros (MDPI AG, 2023)
(1) Background: The present study aimed to examine the relationship between physical activity (PA), screen time (ST), maximal oxygen uptake (VO2max), Mediterranean diet (MD) adherence, self-esteem (SE) and academic performance (AP) in primary education students. In order to address this aim, an explanatory model was developed to examine the existing relationships between PA, ST, VO2max, MD adherence, SE and AP. Further, the proposed structural model was examined via multi-group analysis as a function of sex and school type. (2) Methods: A non-experimental, descriptive, comparative and cross-sectional study was designed with a total sample of 269 Spanish students (11.29 ± 0.62). Validated questionnaires were administered to collect data on study variables. (3) Results: Relative to boys, girls reported better academic grades and showed a stronger positive relationship between MD adherence and AP, MD adherence and PA, and VO2max and SE. Likewise, girls showed a stronger negative relationship between ST and VO2max, and ST and MD adherence. At the same time, mixed funding school (MFS) students reported higher PA engagement than state school (SS) students. However, SS students reported better MD adherence, ST and AP than MFS students. Further, a stronger positive relationship was found in SS students between MD adherence or VO2max and SE than in MFS students. Also, within the former group, ST was more negatively related to MD adherence and VO2max. (4) Conclusions: Scientific and educational communities must develop future strategies that consider potential determinants in order to target more desirable outcomes.